THE PLACE OF THE NARRATOR IN HIS NARRATIVE: A CASE STUDY OF THE WORK OF ALIOUM FANTOURE - Jatoe-Kaleo, Baba Abraham (European Scientific Journal, ESJ, 2013)
This paper seeks to explore the question of the absence of the author/narrator in his work, with particular reference to Le Récit du Cirque…, of Alioum Fantouré. Fantouré in this text, as with his subsequent texts, parodies cruelly the long-held notion that the author should be absent from his work and that as the writing ends, the author ceases to be: dies. The view that the work of art is a heterocosm that must be detached from anything external to it is not upheld by Alioum Fantoure. To him the work of art has a functional purpose: the transformation of society. In Le Recit du Cirqu, he does not any distinction between the dialectically opposed instances of author/reader (in real life) and the narrator/virtual reader in the fictional. In Le Recit du Cirque….he adopts a form of writing that makes the writer/author figure in the fictional world in which he controls all that goes on. He effectively merges the creative work of a novel with factual real life activities such as documentary, film, theatre and telecast of contemporary issues, thus making the writer not only alive, but very much involved in his artistic work.